2010
DOI: 10.1158/0008-5472.can-09-3769
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP Suppression Is Sufficient to Induce Gliomagenesis in a Mouse Model of Neurofibromatosis-1

Abstract: Current models of oncogenesis incorporate the contributions of chronic inflammation and aging to the patterns of tumor formation. These oncogenic pathways, involving leukocytes and fibroblasts, are not readily applicable to brain tumors (glioma), and other mechanisms must account for microenvironmental influences on central nervous system tumorigenesis. Previous studies from our laboratories have used neurofibromatosis-1 (NF1) genetically engineered mouse (GEM) models to understand the spatial restriction of g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 37 publications
3
93
1
Order By: Relevance
“…In contrast, ectopic expression of phosphodiesterase-4 to lower cAMP levels in the forebrain of Nf1 optic glioma mice did lead to glioma formation (Warrington et al, 2010). Interestingly, there are significant variations in the levels of cAMP in different brain regions, with high levels of cAMP in the forebrain compared with the optic nerve (Warrington et al, 2007(Warrington et al, , 2010. Collectively, these findings support the hypothesis that a combination of Nf1 þ /À stromal cell types, permissive cell types and basal signaling levels contribute to the pattern of gliomagenesis in NF1.…”
Section: Stromal Determinants Of Glioma Formation and Growthmentioning
confidence: 76%
See 2 more Smart Citations
“…In contrast, ectopic expression of phosphodiesterase-4 to lower cAMP levels in the forebrain of Nf1 optic glioma mice did lead to glioma formation (Warrington et al, 2010). Interestingly, there are significant variations in the levels of cAMP in different brain regions, with high levels of cAMP in the forebrain compared with the optic nerve (Warrington et al, 2007(Warrington et al, , 2010. Collectively, these findings support the hypothesis that a combination of Nf1 þ /À stromal cell types, permissive cell types and basal signaling levels contribute to the pattern of gliomagenesis in NF1.…”
Section: Stromal Determinants Of Glioma Formation and Growthmentioning
confidence: 76%
“…However, ectopic lentiviral CXCL12 expression in the forebrain of Nf1 optic glioma mice did not induce gliomas with high penetrance (Sun et al, 2010), arguing against CXCL12 as the only spatial determinant important for NF1-associated gliomagenesis. In contrast, ectopic expression of phosphodiesterase-4 to lower cAMP levels in the forebrain of Nf1 optic glioma mice did lead to glioma formation (Warrington et al, 2010). Interestingly, there are significant variations in the levels of cAMP in different brain regions, with high levels of cAMP in the forebrain compared with the optic nerve (Warrington et al, 2007(Warrington et al, , 2010.…”
Section: Stromal Determinants Of Glioma Formation and Growthmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, it has been found that low levels of cAMP expression in the stroma are sufficient to induce optic glioma formation in genetically engineered mouse models of NF1 such that local depletion of cAMP resulted in glioma formation in regions of the brain otherwise not observed to develop tumors (Warrington et al 2010). These findings emphasize the importance of heterogeneity and the cell typespecific effects of various genetic alterations in tumorigenesis.…”
Section: Pi3k Pathwaymentioning
confidence: 99%
“…Last, Nf1 GEM optic glioma models have been particularly instructive in elucidating the requirements for tumorigenesis. Collectively, these studies have revealed that the unique pattern of low-grade astrocytoma development (predominantly in the optic pathway/brainstem of children) reflects the coupling of at least two requirements: (1) Nf1 loss in specific neuroglial progenitor cells (third ventricle or brainstem) during a defined temporal window (embryonic development) (Lee et al 2010(Lee et al , 2012 and (2) a supportive local microenvironment composed of critical molecular signals (Warrington et al 2007(Warrington et al , 2010 and non-neoplastic cell types Daginakatte et al 2008). The current study emphasizes the significant cellular heterogeneity in human NF1-PA, consistent with previous studies on glioma in which a large proportion of the cellular composition is nonneoplastic cells.…”
Section: Discussionmentioning
confidence: 99%